Silver Nanoparticle‐Decorated Reduced Graphene Oxide Nanomaterials Exert Membrane Stress and Induce Immune Response to Inhibit the Early Phase of HIV‐1 Infection. Issue 6 (9th December 2022) - Mukherjee, Soumajit; Bytesnikova, Zuzana; Martin, Sophie; Svec, Pavel; Ridoskova, Andrea; Pekarkova, Jana; Seguin, Cendrine; Weickert, Jean‐Luc; Messaddeq, Nadia; Mély, Yves; Richtera, Lukas; Anton, Halina; et al.
Abstract: Graphene‐based 2D nanomaterials exhibit unique physicochemical, electric, and optical properties that facilitate applications in a wide range of fields including material science, electronics, and biotechnology. Recent studies have shown that graphene oxide (GO) and reduced graphene oxide (rGO) exhibit antimicrobial effects on bacteria and viruses. While the bactericidal activity of graphene‐based nanomaterials is related to mechanical and oxidative damage to bacterial membranes, their antiviral activity has been less explored. Currently available experimental data are limited and suggest mechanical disruption of viral particles prior to infection. In this study, the antiviral properties of reduced GO‐based nanocomposites decorated with Ag nanoparticles (rGO‐Ag) are evidenced against human immunodeficiency virus‐1 pseudovirus used as an enveloped virus model. By combining biochemical and original single virus imaging approaches, it is shown that rGO‐Ag induces peroxidation of pseudoviral lipid membrane and that consequent alteration of membrane properties leads to a reduction in cell entry. In addition, rGO‐Ag is found to be efficiently internalized in the host cell leading to the elevated expression of pro‐inflammatory cytokines. Altogether, the presented results shed new light on the mechanisms of rGO‐Ag antiviral properties and confirm the high potential of graphene derivatives as an antimicrobial material for biomedical applications. Abstract : Silver nanoparticle‐decorated reduced graphene oxide composites (rGO‐Ag) present antiviral activity against human immunodeficiency virus‐1‐based pseudovirus. The results show that rGO‐Ag induce peroxidation of the viral lipid envelope, perturb its biophysical properties, and impede viral entry into the host cell. In parallel, rGO‐Ag are internalized by cells and stimulate the transcription of pro‐inflammatory genes, which most probably contribute to infection inhibition.